Evidence and origin of different types of sedimentary organic matter from a Paleoproterozoic orogenic Au deposit - Mirasol-Robert, A.; Grotheer, H.; Bourdet, J.; Suvorova, A.; Grice, Kliti; McCuaig, T.; Greenwood, P. (Elsevier BV, 2017)
Carbonaceous material (CM) is thought to be a key reductant contributing to the formation of large Au deposits, but there has been much speculation about its source, molecular composition and reactivity. The first successful analytical retrieval of organic compounds from a thermally over-mature ( > 550 °C) Paleoproterozoic Cosmo-Howley Orogenic Au deposit was recently achieved by Robert et al. (2016). Here, we have evaluated the nature of the CM associated with this high temperature Au mineralisation via an integrated analytical approach which combined high-resolution in situ laser Raman spectroscopy, micro to nano-scale imaging (e.g., EELS, HAADF-STEM, and HRTEM) and molecular and isotopic geochemistry. We identified two distinct CM types: CM ker – an ubiquitous highly graphitic kerogen typical of high-grade metamorphic conditions formed by regional metamorphism; and CM fd – small sub-microscopic inclusion-like nodules of highly disordered carbon rich in polycyclic aromatic hydrocarbons (PAHs), coincident within the Au-bearing sulfide minerals in hydrothermal vein regions. The paragenetic emplacement and molecular characteristics of CM fd suggests a formation by metasomatic processes and introduction by a hydrothermal fluid which might also have co-transported Au. CM ker and CM fd gave different Raman spectra indicative of their contrasting origin and structural response to regional and contact metamorphic history and subsequent metasomatism of the Cosmo-Howley deposit. Raman signals indicated CM ker had a graphitic like structure whereas CM fd comprised high concentrations or clusters of PAHs. The broad range of Raman spectra detected here (and by others in similar studies) was likely due to the mixed signals of these two types of CM. The d 13 C values of PAH products released via the HyPy treatment of the parent and sequentially demineralised kerogen fractions were measured to be in the range of -20 to -30‰, indicative of an organic biopolymeric origin. The d 13 C values of PAHs products decreased with demineralisation, concomitant with an increase in their concentrations and affinity to the sulfide-minerals (and associated CM fd ) suggesting a close relationship. The localised (within 20 mm) co-occurrence of different CM types and apparent abundance correlation of CM fd with Au and sulfides suggests Au mineralisation might be supported by specific CM types, and these relationships should be evaluated further including on a wider Au deposit scale.